RSL Fusion with Excision of Distal Scaphoid and Triquetrum: A Cadaveric Study - Bain, Gregory Ian; Sood, Aman; Yeo, Chong Jin (Journal of Wrist Surgery, 2014)
Radioscapholunate (RSL) fusion has been utilized for treatment of radiocarpal arthritis for patients with an intact midcarpal joint. This preserves midcarpal joint motion while alleviating pain. Dart thrower's motion (DTM), which has been emphasized recently, is mainly a midcarpal joint motion.Question A cadaveric study was designed to measure and compare the range of motion (ROM) of the human wrist before and after an RSL fusion, followed by distal scaphoid excision, and finally excision of the triquetrum.Methods Twelve embalmed adult cadaveric upper limbs were assessed. The wrist motion was measured with an electrogoniometer. Measurements of the flexion–extension plane and radial–ulnar deviation plane were obtained for baseline after capsulotomy, after simulated RSL fusion with memory staples, after distal scaphoidectomy, and after excision of the triquetrum.Results The effects of scaphoid and triquetrum excision were expressed as improvements in movement over that of the preceding step. RSL fusion alone resulted in a decrease of the flexion–extension (F-E) arc by 36% and the radioulnar deviation (R-U) arc by 30%. Excision of the distal scaphoid with RSL improved the F-E arc by 34% and the R-U arc by 34%. With excision of the triquetrum, the F-E arc improved further by 13% and the R-U arc by 21%. The ROM of the simulated RSL fusion with distal scaphoidectomy is improved with excising the triquetrum, mainly through an increase in ulnar deviation motion. RSL fusion with distal scaphoidectomy and triquetrectomy can be an alternative to total wrist arthrodesis for patients with an intact midcarpal joint.
Keywords: limited wrist arthrodesis; radioscapholunate fusion; triquetrum excision; carpal excision; distal pole of scaphoid excision